CURSE OR BLESSING: ECONOMIC DIVERSIFICATION AMIDST NATURAL RESOURCE DEPENDENCY IN CENTRAL SULAWESI - Marselius Fransiskus Talahatu; Holiludin Holiludin; Rizka Dzulfikar (EP FEB UNS, 2026)
This study examines the economic structure and structural transformation in 13 regencies/cities in Central Sulawesi Province during the 2013–2023 period. Its primary objective is to evaluate whether the region’s mineral wealth functions as a “blessing” or a “curse” by analyzing the readiness for economic diversification. This study employs a quantitative approach integrating Klassen’s Typology, the Natural Resource Dependency Index (NRDI), the Location Quotient (LQ), and Shift-Share Analysis (SSA-DS). The findings reveal that Morowali and North Morowali Regencies fall into Quadrant I (Advanced and Fast-Growing) but exhibit extreme dependency, with NRDI values exceeding 50. In Morowali, the manufacturing sector serves as the dominant base (LQ=1.90) with high local competitive advantage (DS=72.60), driven by nickel downstream processing. Conversely, North Morowali exhibits a resource paradox where the mining sector is the base sector (LQ=2.51) yet lacks comparative advantage (DS=−2.23), indicating a high risk of the resource curse. To transform natural wealth into a sustainable blessing, Central Sulawesi must prioritize strategic diversification into non-extractive sectors, such as the processing industry (DS=32.26 in North Morowali) and the service sector, supported by institutional reforms and investment in human capital.